Psychometric validation of rasch model for critical reasoning on virus material in high school biology - Nani Aprilia; Hani Irawati; Inrayati Atjo (Universitas Negeri Jakarta, 2026)
Critical reasoning assessment is crucial in supporting deep learning at the high school level, especially in viruses. However, valid and reliable Rasch-based assessment instruments are still very limited. This study aims to validate a critical reasoning assessment instrument based on the Partial Credit Model (PCM) Rasch on viruses in high school biology. The research used a research and development approach with the Plomp model involving 105 Class X students of state high schools in Banguntapan district through purposive sampling.The instrument consisted of 15 polytomous items (scale 0–3) covering four aspects of critical reasoning. Data analysis was conducted using Winsteps software with a focus on item fit (Infit/Outfit MNSQ), difficulty parameters (eta & beta), threshold, separation reliability, and Wright Map. The analysis results showed a separation reliability of 0.7677 (fairly good category). Most items had good variation in difficulty levels, although many items showed disordered threshold patterns. Items P13, P14, and P15 were the most difficult items, while P6, P7, and P8 were the easiest. The findings showed that the instrument was able to differentiate student abilities but still needed revision in the response categories. Recommendations on instrument improvements through simplification of response categories and item writing are needed before widespread use. The instrument has the potential to be a formative diagnostic tool that supports an in-depth learning approach in Biology learning.